PEMBELAJARAN STATISTIKA MELALUI PROJECT BASED LEARNING DENGAN BANTUAN MICROSOFT EXCEL UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK VIII D SMPN UNGGULAN SINDANG INDRAMAYU - Herawati , Eti (Universitas Wiralodra, 2017)
The aim of this research is to improve the learning outcomes of VIIID students of SMP Negeri Unggulan Sindang Indramayu school year 2014/2015 on Statistic material through Project Based Learning Model-Aided Microsoft Excel. The subjects of this research is VIII D students of SMP Negeri Unggulan Sindang Indramayu school year 2014/2015, consist of  30 students, 19 girls and 11 boys. Data collection techniques in this study using observation sheets, tests, observations, questionnaires, interviews and documentation. Statistics attitude towards learning through Project Based Learning Model-Aided Microsoft Excel mostly been good and very good. Can be seen the percentage of successful the first cycle increased from 86.67% to 100% in the second cycle. Percentage mastery learning outcomes in mathematics learning competency skills is increase. The percentage of successful at first cycle increased from 73% to 86.67% in the second cycle. Learning outcomes based on knowledge an increasing number of which reached KKM cycle I to cycle II. KKM percentage reached 76.67% in the first cycle increased to 86.67% in the second cycle. Based on the research that has been conducted, statistics learning using Project Based Learning Model-Aided Microsoft Excel is able to improve the learning outcomes of class VIIID students of SMP Negeri Unggulan Sindang Indramayu school year 2014/2015. The application of statistical learning using Project Based Learning Model-Aided Microsoft Excel as an alternative model of learning that can be applied to topics and other subjects but required good planning and proper time management.